The People's Plaza : sixty-two days of nonviolent resistance - Jones, Justin, 1995- (Vanderbilt University Press, 2022)
"A first-person account of the two month stand-off in 2020 between protesters and state troopers, Metro police, and the National Guard at Ida B. Wells Plaza in Nashville"--